2017
DOI: 10.4414/smw.2017.14488
|View full text |Cite
|
Sign up to set email alerts
|

A mini-overview of single muscle fibre mechanics: the effects of age, inactivity and exercise in animals and humans

Abstract: Many basic movements of living organisms are dependent on muscle function. Muscle function allows for the coordination and harmonious integrity of movement that is necessary for various biological processes. Gross and fine motor skills are both regulated at the micro-level (single muscle fibre level), controlled by neuronal regulation, and it is therefore important to understand muscle function at both micro- and macro-levels to understand the overall movement of living organisms. Single muscle mechanics and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…At the same time, other investigators have only shown a numerically yet non-significantly higher maximal Ca 2+ activated force produced by MHC II fibers in trained individuals ( Trappe et al, 2001 , 2006 ; Harber et al, 2004 ; Luden et al, 2012 ). In less trained individuals, this inconsistency also exists with fiber type differences observed in some but not all studies – for review see ( Jee and Kim, 2017 ). Reasons for these slight inconsistencies between studies in trained athletes are not clear but may be related to methodological differences (e.g., skinning process, temperature or the composition of the activating solutions), a lack of statistical power needed to detect a difference, different sport-specific demands, or different muscles of investigation.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, other investigators have only shown a numerically yet non-significantly higher maximal Ca 2+ activated force produced by MHC II fibers in trained individuals ( Trappe et al, 2001 , 2006 ; Harber et al, 2004 ; Luden et al, 2012 ). In less trained individuals, this inconsistency also exists with fiber type differences observed in some but not all studies – for review see ( Jee and Kim, 2017 ). Reasons for these slight inconsistencies between studies in trained athletes are not clear but may be related to methodological differences (e.g., skinning process, temperature or the composition of the activating solutions), a lack of statistical power needed to detect a difference, different sport-specific demands, or different muscles of investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the locomotory apparatus loses its effectiveness, due to the molecular and cellular changes occurring in the myofascia, the skeletal muscle tissue, the nervous system, and their structural and functional coupling. Genetics, epigenetics, environment, diseases, lifestyle, nutrition, and injuries also have a prominent role in tissue remodeling occurring with aging (Jee and Kim, 2017). Thanks to recent scientific progress, many phenomena and mechanisms associated with aging have been defined, but still much remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies indicate a negative effect of aging also on skeletal muscle plasticity, which is the potential of this tissue to modify its structural and functional features in response to environmental changes (Verdijk et al, 2007;Jee and Kim, 2017;Suetta, 2017). The regrowth response to physical inactivity-induced atrophy is also hindered in aged muscles (Pisot et al, 2016).…”
Section: Skeletal Muscle and Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, others have suggested that remaining muscle fibres are not weaker [14,15], possibly due, at least in part to the fact that this loss is not consistent across the whole body. Thus, whether a defect occurs at the level of the single fibre remains unclear, with studies showing conflicting findings (see [16] for review).…”
Section: Ageing Is Associated With a Decline In Skeletal Muscle Strucmentioning
confidence: 99%